Neptunyl(vi) centred visible LMCT emission directly observable in the presence of uranyl(vi). Issue 25 (22nd December 2014) - Woodall, Sean D.; Swinburne, Adam N.; lal Banik, Nidhu; Kerridge, Andrew; Di Pietro, Poppy; Adam, Christian; Kaden, Peter; Natrajan, Louise S.
Abstract : The room temperature detection of neptunyl(vi ) LMCT emission in a coordination compound and in the presence of uranyl(vi ) is reported for the first time. Differences in the excitation profile of each complex enables spectral editing of the neptunyl(vi ) and uranyl(vi ) emission. Abstract : Room temperature detection of neptunyl(vi ) LMCT emission in a coordination compound and in the presence of uranyl(vi ) is reported for the first time. Differences in the excitation profiles of the complexes enable spectral editing so either exclusively neptunyl(vi ) or uranyl(vi ) emission is observed or a sum of the two.